Կորստի մորմոք, նահանջ, ներգաղթելու հույս եզրույթը Պետրոս Հաճյանի «Հրամմեցէ՛Ք, պարոններ» պատմվածաշարում - Դավթյան, Ն.
Статья представляет собой скромную попытку оценить литературную деятельность аргентинского известного педагога, писателя, прозаика Петра Ачяна посвятивщего себя Ай Дат. Многотомное литературное наследие П.Ачяна включает в себя изучение рассказов, книг, издательских статей и литературоведческих исследований. Он был одним из первых, кто наряду с горечью потери страны, вечной ностальгии, затронул в литературе тему иммиграции и заговорил о надеждах и ожиданиях разбросанных по всему свету армян. The article is a modest attempt to assess the activities of the Argentine literary renowned educator, writer, novelist Peter Achan, who has devoted himself to Hay Dat. Literary heritage of P.Achyan is multivolume, it includes the study of short stories, books, publishing articles and literary studies. Along with sorrow of the country loss and the eternal nostalgia he touched on the theme of immigration in the literature, and spoke of the hopes and expectations of Armenians scattered all over the world.
Keywords: Գրականագիտություն